A Low-Grade Angiomyxofibromatous Tumor of the Falx Cerebelli: A Mimic of Fourth Ventricular Tumors - Modi, Parth P.; Rohra, Vinay; Patel, Parth Anand Kumar; Kachchhi, Udayan (Asian Journal of Neurosurgery, 2025)
Low-grade fibromyxoid tumors are very uncommon in children. A tumor of this type has never been reported in the posterior fossa to date. Such lesions may mimic more common lesions of the posterior fossa. Awareness of this entity and its subsequent behavior may guide better management and outcomes. We describe the case of a previously unreported low-grade angiomyxofibromatous tumor of the falx cerebelli in a 10-year-old female, whose presentation mimicked cystic lesions of the posterior fossa causing obstructive hydrocephalus. Microscopic examination revealed stellate cells set in myxoid and edematous stroma, along with a plexiform vasculature pattern. The tumor cells were diffusely immunopositive for vimentin and focally positive for S-100 protein, but negative for epithelial membrane antigen, CD34, MIC2, Bcl-2, glial fibrillary acidic protein, cytokeratin, CAM 5.2, desmin, and smooth muscle actin. This lesion could not be categorized according to the current World Health Organization classification of tumors of the nervous system. Therefore, there is a need for a better understanding of the central nervous system (CNS) myxoid neoplasms and a reassessment of the classification of CNS tumors.
Keywords: angiomyxofibromatous; falx; mimic; obstructive hydrocephalus; posterior fossa